Desmosis coli as an extremely rare cause of constipation in children – case report and mini-review - Jakub Kucharski; Aldona Ząber; Brygida Zapała; Barbara Skowrońska; Magdalena Dobrowolska; Justyna Konys; Dariusz Piotrowski; Aleksandra Banaszkiewicz; Marcin Banasiuk (Pediatria Polska, 2023)
Desmosis coli (DC) is an extremely rare condition of unknown pathogenesis. Only a few cases have been reported in the literature. It is characterised by the absence of connective tissue between muscle layers in the colon. Chronic constipation is the main manifestation of DC; thus, it largely resembles Hirschsprung disease. Moreover, neither DC nor Hirschsprung disease responds to conventional treatment. This paper describes a case of a patient with a diagnosis of DC. It was written to highlight the importance of proper diagnosis and to raise awareness of this uncommon disorder. A mini-review of the literature on DC is also provided.